Improving driver loyalty through using gamification approach - Mogie, Callista Ivana; Ricky, Ricky; Wang, Gunawan; Sfenrianto, Sfenrianto; Azlee, Zabidi; Gui, Anderes (Institute of Electrical and Electronics Engineers Inc., 2023)
Better staff motivation is believed enables to deliver better performances. Although it sounds essential, many companies have carried out unsuccessful program to do so. The article examines improving gamification design in Gojek app, a pioneer of ride hailing company, in Indonesia. Studies show the use of Gamification has proven to deliver many benefits and improve better performances in business. The article applies game design approach in Gojek app to improve driver's motivation as key factor to improve overall company performance. The article applies Maslow needs theory to guide the game design to improve overall drivers' motivation, loyalty, and achievements.